ChemInform Abstract: Clean Solid Biofuel Production from High Moisture Content Waste Biomass Employing Hydrothermal Treatment. Issue 3 (29th December 2015) - Zhao, Peitao; Shen, Yafei; Ge, Shifu; Chen, Zhenqian; Yoshikawa, Kunio
Abstract: Review: 268 refs.